Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1007/s12035-012-8375-5
|View full text |Cite
|
Sign up to set email alerts
|

A Non-transgenic Mouse Model (icv-STZ Mouse) of Alzheimer’s Disease: Similarities to and Differences from the Transgenic Model (3xTg-AD Mouse)

Abstract: Alzheimer’s disease (AD) can be divided into sporadic AD (SAD) and familial AD (FAD). Most AD cases are sporadic and result from multiple etiologic factors, including environmental, genetic and metabolic factors, whereas FAD is caused by mutations in the presenilins or amyloid-β (Aβ) precursor protein (APP) genes. A commonly used animal model for AD is the 3xTg-AD transgenic mouse model, which harbors mutated presenilin 1, APP and tau genes and thus represents a model of FAD. There is an unmet need to in the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
156
2
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 239 publications
(204 citation statements)
references
References 60 publications
28
156
2
3
Order By: Relevance
“…In comparison to AD, in VaD, human brain neurotransmitter alterations are mild, e.g., for choline acetyltransferase activity, muscarinic receptor density, serotonin, dopamine, homovanillic acid, dopamine D1-and D2-receptor density, noradrenaline, and gamma aminobutyric acid (GABA), while 5-hydroxyindoleacetic acid (5-HIAA) shows a more pronounced deficiency. This data summarized here agree in principle with more recent conclusions of post-mortem human brain studies and experimental models (Ohara et al 1994;Pimlott et al 2004;Jia et al 2004;Tohgi et al 1996;Chen et al 2013;Lee et al 2014;Niwa et al 2002;Pedrós et al 2014;Knezovic et al 2015;Barilar et al 2015). CSF concentrations of choline were significantly higher in VaD patients compared to AD and controls but did no correlate with mini-mental state examination (MMSE) scores (Jia et al 2004;Tohgi et al 1996).…”
Section: Pathologysupporting
confidence: 92%
See 1 more Smart Citation
“…In comparison to AD, in VaD, human brain neurotransmitter alterations are mild, e.g., for choline acetyltransferase activity, muscarinic receptor density, serotonin, dopamine, homovanillic acid, dopamine D1-and D2-receptor density, noradrenaline, and gamma aminobutyric acid (GABA), while 5-hydroxyindoleacetic acid (5-HIAA) shows a more pronounced deficiency. This data summarized here agree in principle with more recent conclusions of post-mortem human brain studies and experimental models (Ohara et al 1994;Pimlott et al 2004;Jia et al 2004;Tohgi et al 1996;Chen et al 2013;Lee et al 2014;Niwa et al 2002;Pedrós et al 2014;Knezovic et al 2015;Barilar et al 2015). CSF concentrations of choline were significantly higher in VaD patients compared to AD and controls but did no correlate with mini-mental state examination (MMSE) scores (Jia et al 2004;Tohgi et al 1996).…”
Section: Pathologysupporting
confidence: 92%
“…Cerebrovascular functions and AN both decline during aging (Kalaria 2009;Kempermann 2015) which stands to reason as AN occurs within an angiogenic niche (Palmer et al 2000). Improved energy supply in experimental AN studies show improved AN when using DM related therapeutic strategies (Luitse et al 2012;Biessels 2013;Sonnen et al 2009;Jia et al 2004;Tohgi et al 1996;Chen et al 2013;Lee et al 2014;Niwa et al 2002), indicating an important role of glucose/energy supply for the proper integrity of AN physiology.…”
Section: Future Strategiesmentioning
confidence: 99%
“…Shoham et al (2007) and Espinosa et al (2013) have reported recognition memory impairments in icv-STZ-treated rats, and a comparative study between rodent models of sAD (Chen et al, 2013) has shown that the icv-STZ model is even more detrimental to short-term memory than the transgenic 3xTg-AD mouse model. In line with the icv-STZ impact on cognition, spatial discrimination impairments in STZtreated animals were shown to correlate with reduced choline acetyltransferase (ChAT) activity in the hippocampus (Blokland and Jolles, 1993;Prickaerts et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…STZ-icv model has additionally been reported to develop also cerebral amyloid angiopathy in rats (appearing at 3 months and progressing up to 9 months after the STZ-icv) (Salkovic-Petrisic 2006;Salkovic-Petrisic 2011) and congophyllic amyloid deposition in mice (1 month after STZ-icv) (Sodhi et al 2013, Wang et al2014 as well as increased hippocampal APP mRNA after 4 weeks in rats (de la ) and normal APP mRNA expression 5 months after STZ-icv treatment in monkeys (Lee et al 2014, Park et al 2013). All were explored in STZ-icv model mostly at one time point only, usually up to 1 or 3 months after the STZ-icv treatment in rats and mice (Agrawal et al 2010, Agrawal et al 2011, Schido et al 2013, Deng et al 2009, Sodhi et al 2013, Wang et al 2014, Chen et al 2013Chen et al2014) and up to 5 months in monkeys (Lee et al 2014;Park et al, 2013;Heo et al 2011). Periods longer than 5 months post-STZ-icv injection have not been explored in regard to the brain insulin system in STZ-icv model of sAD.…”
Section: Introductionmentioning
confidence: 99%